Achieving physical examination competence through optimizing hands-on practice cycles: a prospective cohort comparative study of medical students - Zinan Zhang (PeerJ Inc., 2021)
Background Deliberate practice (DP) was proposed for effective clinical skill training, which highlights focused, repetitive practice and feedback as the key points for practice. Although previous studies have investigated the effect of feedback in DP, little is known about the proper repetitive cycles of clinical skills training especially in physical examination (PE) training. Methods We drew learning curves and designed a comparative study to find out the optimal number of hands-on practice cycles, an important aspect of DP, in abdominal PE training for medical students. A comparative study was conducted to validate the optimal number of hands-on practice by dividing students into two cohorts including Cohort A (high-frequency hand-on training) and B (low-frequency hand-on training). Results The learning curve study of 16 students exhibited a threshold of four repetitive practices when 81.25% students reached the competence score. A total of 74 students’ final exam scores were collected for analysis. Students in Cohort A (4–5 PEs) scored significantly higher than those in Cohort B (≤3 PEs) (84.41 ± 11.78 vs 76.83 ± 17.51] in the final exam (P = 0.030)). Conclusion High-frequency practice can improve students’ competence of abdominal PE skill. We recommend four cycles of hands-on practice for each student in a training course like PE training.